Evaluación del uso de lodos base aceite para la perforación de la sección intermedia de pozos en un bloque al sur del Putumayo (2020)
In this work, the use of the mud system used in the drilling of the intermediate section of wells A, B, C and E of diameter 12 1⁄4 ”and of well D of diameter 8 1⁄2” was evaluated in a block south of Putumayo. For this, the cuttings obtained in this operation were used and they were taken to the laboratory to carry out tests of the oil-based drilling fluids for wells A and B and water-based for wells C, D and E as density, rheology, capacity of cation exchange, linear swelling, lubricity, among others.